Emotional Intelligence as A Factor in Work Related Outcomes â€“ A Study Among The Paramedical Staff at SRM Medical College, Kattankulathur, Chennai. - Lokeswara Choudary, Dr. Y. (Journal of Contemporary Research in Management (JCRM), 2013)
The nursing profession demands that the nurse, in the process of care, has to interact with the patients, the medical fraternity and the health care workers constantly. Hence, â€œNurse-Patient Interactionâ€ is the pulse of the nursing practice. This interaction is not just conversation. It is a complex process that involves nurse perception, understanding of the patient emotions and utilization of the perceptions to manage patient situations towards the goal of effective patient care. Emotional intelligence plays a major role in doing the same. Emotional Intelligence has four main components, namely, the ability to: 1. Perceive emotions; 2. Utilize these emotional perceptions to accomplish various activities or tasks; 3.Understand emotional variations; and 4. Manage emotions to achieve goals. Thus, Emotional Intelligence is a measure of an individualâ€™s capability and requires tools to assess this capability. Developing emotional intelligence requires that we unlearn old habits of thought,Â  feeling, and action that are deeply ingrained, and grow new ones. Such a process takes motivation, effort, time, support, and sustained practice. An attempt has been made in this study to identify the determinant factorsÂ  that influence the emotional intelligence as depended variable. The present study is focused on two major objectives namely: to study the significant impact of Emotional intelligence on behavior of nurses and to analyze the role of Emotional intelligence in work-related outcomes. TheÂ  present study in explored on all aspects of work and work related issues affecting work efficiency and emotional intelligence of the nursing staff. The primary reasons for emotions at work place are heavy work load,Â  working conditions. The solution to reduce the emotional levels of the nursing staff is clearly discussed in the study.